2020
DOI: 10.1364/oe.393887
|View full text |Cite
|
Sign up to set email alerts
|

Electronic measurement of femtosecond time delays for arbitrary-detuning asynchronous optical sampling

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(45 reference statements)
0
8
1
Order By: Relevance
“…A certain number n of measurement points is fit to a model function in order to average out the noise in the single-shot data. We implemented a linear fit only since ref has shown that higher-order fits, which might account for drifts in the oscillator frequencies, yield only a minor improvement of the final accuracy, and only if time-delays longer than the one anticipated here is used (i.e., 400 μs corresponding to the 2.5 kHz repetition rate of our Ti:Sa amplifier). That is, we fit the unwrapped data t i to: t i = 0 + Δ × i where i = 0, ..., n – 1 indexes the measurement, n is the number of measurements that go into the fit, t̂ 0 is the starting value for the first measurement point i = 0, and the slope Δ t̂ is the change of time-separation per measurement point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A certain number n of measurement points is fit to a model function in order to average out the noise in the single-shot data. We implemented a linear fit only since ref has shown that higher-order fits, which might account for drifts in the oscillator frequencies, yield only a minor improvement of the final accuracy, and only if time-delays longer than the one anticipated here is used (i.e., 400 μs corresponding to the 2.5 kHz repetition rate of our Ti:Sa amplifier). That is, we fit the unwrapped data t i to: t i = 0 + Δ × i where i = 0, ..., n – 1 indexes the measurement, n is the number of measurements that go into the fit, t̂ 0 is the starting value for the first measurement point i = 0, and the slope Δ t̂ is the change of time-separation per measurement point.…”
Section: Methodsmentioning
confidence: 99%
“…The central synchronization electronics is shown as schematics in Figure c and a picture of a prototype in Figure d. It is conceptually the same as that of ref , but quite different in its realization. The pulse trains from the two laser oscillators are fed in by optical fibers, with fast photodiodes directly mounted on the printed circuit board (PCB) to minimize electric noise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional ASOPS approach is a stroboscopic method based on two femtosecond oscillators with nearly identical repetition frequencies or near multiples. However, over the past decade, the Joffre group demonstrated an arbitrary-detuning ASOPS (AD-ASOPS) that utilizes two oscillators with arbitrarily different repetition frequencies. Their AD-ASOPS does not require dedicated oscillators specially set up for conventional ASOPS. An early version of AD-ASOPS was based on an interferometric detection of coincidences between pulses to measure the pump–probe delay time a posteriori . , More recently, they showed that a couple of photodetectors and a time-to-digital converter combined with a frequency divider and a pulse selector could be used to enable a high-rate electronic measurement of the delay between pump and probe pulses .…”
Section: Conventional Nonlinear Spectroscopy With a Single Mode-locke...mentioning
confidence: 99%
“…44,45 More recently, they showed that a couple of photodetectors and a time-to-digital converter combined with a frequency divider and a pulse selector could be used to enable a high-rate electronic measurement of the delay between pump and probe pulses. 47 This technique was teremed optoelectronic AD-ASOPS. The AD-ASOPS is an exciting variant of ASOPS because one can use even amplified systems with a few kilohertz to tens of kilohertz repetition frequencies for monitoring slow chemical or biological processes on a broad range of time scales from picoseconds to milliseconds.…”
mentioning
confidence: 99%